Nietzsche as precursor of postmodern translation studies - Chen, Liming (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
Friedrich Nietzsche is generally considered the precursor of postmodern philosophy (Erickson 2001: 84), the basis of which are: Antichrist (rejection of all attachment to God) and a call for a re-evaluation of all values, a negation of conventional metaphysics, an insistence on perspectivism, a rejection of Enlightenment rationality and the advocation of will to power. Nietzsche’s postmodern philosophy and his thought on translation play a fundamental role in postmodern translation studies, uncrowning the author as God of the text, liberating the translator, and enlarging the space of multi interpretative signifiers. Meanwhile, his insights have helped extricate translators from ethical questions about their re-creativity, encourage them to develop a translator’s subjectivity and consequently broaden the horizon of translation studies. Such radical thoughts as perspectivism in interpretation, re-evaluation of Christian values, a historical sense of the past, and the conquest of the Ancient, especially by translation, can also be applied to his thoughts on translation (studies), though not so systematic as they are, initiating an inspiring postmodern approach to translation studies, and exerting a lasting and profound influence on his followers like Heidegger, Gadamer, Benjamin, Pound, Derrida, Steiner, Lefevere, Venuti, etc. An elaborative review of Nietzsche’s insightful ideas as such should clarify the genealogy of postmodern translation studies in general.